Hg(II) sensing, catalytic, antioxidant, antimicrobial, and anticancer potential of Garcinia mangostana and α-mangostin mediated silver nanoparticles. (June 2021) - Jamila, Nargis; Khan, Naeem; Bibi, Nousheen; Waqas, Muhammad; Khan, Sadiq Noor; Atlas, Amir; Amin, Farhat; Khan, Faryal; Saba, Malka
Abstract: This study reports synthesis of Garcinia mangostana fruit pericarp (unwanted waste material) and α -mangostin mediated silver nanoparticles (AgNPs). These AgNPs were efficiently produced using 1:10 (extract and salt) ratio under stirring and heating, which was confirmed by surface plasmon resonance (SPR) band in UV–Visible spectroscopic analysis, and size of 73–91 nm determined by scanning electron microscopy (SEM) and atomic force microscopy (AFM). The synthesized AgNPs were used for Hg(II) detection in tap water, where the limits of detection and quantification were 2.6 μM and 8.9 μM, respectively. Furthermore, the subject AgNPs showed promising catalytic activity in the reduction of dyes and food colours including Congo red (CR), methylene blue (MB), malachite green (MG), methyl orange (MO), para -nitrophenol (PNP), rhodamine B (RdB), zarda yellow (ZY), deep green (DG), and bright red (BR). The synthesized AgNPs were also evaluated for their antioxidant, antimicrobial, and anticancer properties, where α -mangostin and its nanoparticles (Mang-AgNPs) exhibited promising IC50 values of 14.1 and 13.5 μg/mL, respectively against DU-145 cell line validated by in silico molecular docking study. This study is the first report highlighting the application of AgNPs of G. mangostana fruit pericarp extracts, and α -mangostin in Hg(II) detection, dyes degradation, and anticancer potential against DU-145. Finding of this study suggested the suitability of AgNPs as promising solid biosensor in Hg(II) metal detection, dyes reduction, and target in anticancer drug development. Graphical abstract: Image 1 Highlights: Synthesis of G. mangostana and α-mangostin AgNPs. Hg(II) sensing by synthesized AgNPs in real tap water samples. Catalytic property of synthesized AgNPs. Significant anticancer activity against DU-145 cell line by subject AgNPs. Validation of anticancer activity via molecular docking analysis.